Children's voices in early childhood education and care - Correia, N.; Aguiar, C. (Establishing child centred practice in a changing world: Part B, 2023)
Listening to and considering children’s voices shows respectful regard for children’s needs, interests and experiences, and helps discern what is meaningful for them in a particular subject or situation. Creating opportunities for the expression of children’s voices implies child-centred practice: recognising children as active agents, with evolving competences and capacity to understand, think and choose with some degree of autonomy, thus being able to influence decision-making. Therefore, the commitment to listen to children’s voices represents a fundamental step towards empowering children and supporting their participation rights. Importantly, children have the right to be heard and to have their voices considered from the earliest ages, in their significant relational contexts, such as early childhood education and care (ECEC). Listening to and valuing children’s multiple voices in ECEC can be done in many ways, ensuring the context, children’s background, characteristics and preferences are respected. In this chapter, we address the specificities of listening to children’s voices and taking them into account in ECEC. We discuss common challenges that may prevent the full expression and consideration of children’s voices, and ways to overcome them, to ensure children’s meaningful participation in what matters to them and support them in becoming active citizens in society.